Road crash and injury of bus and taxi drivers in Hanoi, Vietnam - La, Quang Ngoc (Curtin University, 2011)
Injury due to road traffic crash is a major cause of ill health and premature death in developing countries for adult men aged 15-44 years. Previous studies have focused on different road user groups, such as pedestrians, bicyclists, motorcyclists and motor vehicle drivers. There is relatively little research examining the risk of crashes for bus and taxi drivers, particularly in developing countries. This study aims to profile the crash characteristics among bus and taxi drivers, and to investigate the risk factors for road traffic crash in Hanoi, Vietnam.The study consisted of two phases. In the first phase, a retrospective study was undertaken to estimate the prevalence of road traffic crashes (RTCs) by bus and taxi drivers over the past three years (from 2006 to 2009), and to collect baseline information on their crash characteristics. The behaviour and lifestyle of 1579 drivers (365 bus and 1214 taxi drivers) in Hanoi were documented. During the second phase, the identified cohorts were followed up for 12 months. The objective of the prospective study was to assess the incidence of road traffic crash and the underlying exposure, type and severity of injuries, so that pertinent risk factors of road traffic crash for these drivers can be identified.The study subjects consisted of 365 bus drivers and 1214 taxi drivers in Hanoi, Vietnam. Face-to-face interviews were conducted by the author and research team using a structured questionnaire to: collect information on demographic and lifestyle characteristics; record the history of road traffic crash for a period of three years (2006 to 2009) and detail crash characteristics during a 12 month follow up (2009 to 2010).The main findings of the first phase of study involving 1214 taxi drivers showed that the mean age of drivers was 31.9 (Standard Deviation (SD) = 6.8) years. The mean working years as taxi drivers was 2.59 (SD: 2.3) years, with the longest duration being 15 years and shortest being two months. The travelling distance of each driver ranged from 80 kilometres to 350 kilometres, with a mean of 182.2 (SD: 48.5) kilometres per working day. The percentage of drivers who were smokers was 54.4%, and 60.7% of drivers had not consumed alcohol within the last month.A total of 276 taxi drivers were involved in 336 RTCs with a prevalence of 27.7% for a period of three years. Ninety three (27.7%) crashes resulted in hospitalization. Results of logistic regression analysis found that the age of drivers (Odd Ratio (OR) = 0.95, 95% Confidence Interval (CI): 0.92 to 0.97), type of driving license (OR = 1.56; 95% CI: 1.17 to 2.09), full-time employment status (OR = 2.22; 95% CI: 1.09 to 4.54), insufficient income (OR = 1.44; 95% CI: 1.08 to 1.93), never wore a seat-belt (OR = 1.69; 95% CI: 1.04 to 2.44), and traffic infringement history (OR = 1.87; 95% CI: 1.30 to 2.71), were significantly associated with RTCs.After the 12 month follow up, 225 (18.5%) of 1214 taxi drivers had dropped out due to change of job and/or lack of follow up contact details. The 11.9% of drivers (145 drivers) have been involved in at least one RTC within 12 months. Among these 145 drivers, only three drivers reported to involve in two crashes. Cumulative Incidence rate was 0.122 in 12 months.The crashes between taxi drivers and motorcyclists accounted for 59.5% of crashes. A high percentage of crashes (89.9%) occurred on street roads and 10.1% on the highway. Crash incident on straight and level roads was 71.6%. Crashes in dry conditions accounted for 75.7%, with 62.2% of crashes happened in daylight. Of 148 crashes, 39.9% had at least one hospitalised person (accounted for either drivers or other crash victims), with 8.1% of crashes accounting for two hospitalised persons. The results of logistic regression analysis in the follow up period indicated that only suffered from tiredness increased the risk of RTC for taxi drivers. The risk of hospitalisation as the outcome of crash led to identification of three significant factors, namely: crashes happened in rush hours (OR = 2.24, 95% CI: 1.00 to 5.03), crashes between taxi and motorbike (OR = 7.28; 95% CI: 2.87 to 18.42), and crashes happened in curve or hillcrest roads (OR = 2.68; 95% CI: 1.00 to 6.80).The 365 bus drivers were all male and recruited from five bus companies in Hanoi. Three quarters of the bus drivers were less than 45 years old. The mean age of the bus drivers was 39.2 (SD: 7.2) years old. The mean working years as bus drivers was 6.77 (SD: 4.6) years. The percentage of drivers who were in full-time employment was 75.6%. The average travel distance of each driver was 175.1 (SD: 37.2) kilometres per working day.More than 50% of bus drivers were smokers. Among smoking drivers, 6.1% smoked more than 20 cigarettes per day. Drivers who had drunk at least one standard drink in the last month accounted for 68.8% of all drivers and 66.0% of drivers had made a phone call when driving a bus. Only 10.2% of bus drivers always wore a seat-belt.In the last three years, 73 bus drivers involved in 76 RTCs. The RTC prevalence was 20.8%, with 73.7% of crashes resulting in hospitalisation. Among these 73 drivers, three (4.2%) drivers were involved in two crashes during the last three years. Crashes mainly occurred on local streets/roads (80.9%).Logistic regression analysis to explore the contributing factors of RTC resulted in two significant factors namely: migrant worker (OR = 4.26; 95% CI: 2.20 to 8.25) and insufficient income (OR = 2.6; 95% CI: 1.37 to 4.93). The results of Poisson regression between the number of crashes and other variables indicated two contributing factors. They were type of worker (Incidence-Rate Ratio (IRR) = 2.89; 95% CI: 1.67 to 4.98), and adequacy of income (IRR = 1.73; 95% CI: 1.03 to 2.94). The migrant workers were likely to be involved in more RTCs than others, and drivers who reported earning insufficient money for their family were also likely to be involved in more RTCs compared to others drivers.Within 12 month follow up of 365 bus drivers, there were 39 (10.7%) drivers in loss to follow up condition. A total of 109 drivers have ever involved in at least one RTC in this follow up duration. Among the crash drivers, 96.4% were involved in one crash. Cumulative Incidence rate of RTC of this cohort of bus drivers in 12 months was 0.304.Up to 13.5% of crashes happened during rush hour (from 6 AM to 8 AM and from 5 PM to 6 PM). Crashes where there was a collision between buses and motorbikes accounted for 53.5%, and 3.6% between buses and pedestrians or passengers, and 93.7% of crashes occurred in the local street/road areas, as opposed to only 0.9% on the highway. With regard to the gradient of the road, 47.7% of crashes were in straight and level roads, 30.6% in curved and grade/hillcrest roads, and 11.7% in curved and level roads. Crashes occurring during daylight accounted for 65.8% with 68.5% in dry conditions, and 54.1% in crowded road conditions.Results of logistic regression of RTC during follow up time indicated two statistically significant factors; they were migrant drivers and insufficient income drivers. Results of logistic regression, for risk factors of severity of crash indicated two significant factors, which were types of vehicles/objects of crash, and weather condition at the time of crash. Crashes happening due to bus and motorbike collision were more likely to result in a person being hospitalised, than other subjects involved in collision (OR = 6.65; 95% CI: 2.20 to 20.16). Crashes in wet weather were more likely to result in a hospitalised person (OR = 3.36; 95% CI: 1.11 to 10.10).There are some limitations that need to be considered when interpreting the findings of the study. For the retrospective study, prevalence of RTCs did not include bus and taxi drivers, who left the profession prior to the survey because of crashes or other reasons. The possibility of recall bias based on self-reports was another issue. For the prospective study, new drivers who entered the profession were excluded in the follow up. Moreover, in the 12 month follow up, tracking the cohorts and loss to follow up posed a difficulty for interpreting the results.The main recommendation of the study was the need to conduct a qualitative survey to identify the root causes and perceptions of bus and taxi drivers in relation to the RTCs. Physical health outcomes may mediate the relationship between stress and crash outcomes. Studies on physical health of drivers and its association with crashes are needed. Their working conditions should be further explored in relation to the level of workload, and extra work to provide them with sufficient income. Moreover, it is recommended to investigate RTCs of bus and taxi drivers from the perspective of other road users. An intervention should then be implemented to improve the safety of these drivers.